Entrepreneurship and creation of new business: key factors of Brazilian entrepreneurial ecosystem - Souza, Lucas Lopes Ferreira de; Gerhard, Felipe; La Rovere, Renata Lèbre; Câmara, Samuel Façanha (Revista de Negócios, 2016)
This article aims to analyze the profile of Brazilian entrepreneurs and the factors that shape the entrepreneurial ecosystem in this country. A survey was conducted with 76 Brazilian entrepreneurs from the ICT sector, which was chosen because of its high growth rates. The research was developed in the context of a joint project called Entrepreneurship and New Venture Creation that involves universities from five countries: Italy, Brazil, Russia, India and China. The project has as objective to study the key factors of entrepreneurial ecosystem that facilitate the growth of knowledge intensive business in each country. The methods exploratory factorial analysis and non-hierarchy cluster K-means were used in order to reach the research objectives. From the analysis of the results, three groups of entrepreneurs with distinct profiles emerged. The data also reveals that the social elements are more important than the personal issues and public policies have an essential role in the development and maintenance of the entrepreneurial ecosystem in Brazil. As limitations, we consider that the low quantity of entrepreneurs can jeopardize the generalization of the findings. The replication of this research and the performing of cross-cultural studies are presented as suggestions for future research that can resolve this limitation. The new concepts of Brazilian entrepreneurs based on a large and applied entrepreneurial scale constitute the study originality.